Early post-stroke seizures in acute ischemic stroke: A prospective cohort study - Ayush Agarwal; Jyoti Sharma; M V Padma Srivastava; Rohit Bhatia; Mamta Bhushan Singh; Anu Gupta; Awadh K Pandit; Rajesh Singh; Roopa Rajan; Sadanand Dwivedi; Ashish Upadhyay; Ajay Garg; et al. (Annals of Indian Academy of Neurology, 2021)
Introduction: Stroke is the most common cause of epilepsy in the adult population. Post-stroke seizures (PSSs) are classified into early-onset seizures (ES) and late-onset (LS). ES can significantly affect the clinical outcome and occurrence of LS. Methods: We analyzed data from a prospective cohort of acute ischemic stroke patients between June 2018 and May 2020 in a neurology unit at a tertiary hospital. We screened all acute stroke patients and included consecutive patients older than 18 years of age, presenting with acute, first-ever neuroimaging-confirmed ischemic stroke. We excluded patients with a previous stroke, transient ischemic attacks, hemorrhagic stroke, cerebral venous thrombosis, prior history of seizures, or any other epileptogenic comorbidity. ES were classified as spontaneous seizures occurring within 1 week of the stroke. The main outcome assessed was the occurrence of ES. The secondary outcome was to determine predictors of ES and create an ES prediction score. Results: We screened 432 patients; of them, 291 were enrolled. ES occurred in 37 patients (12.7%). Cortical location (OR: 4.2), large artery disease subtype (OR: 2.9), mRS at presentation (OR: 1.4), use of anticoagulants (OR: 2.6), and hypertension (OR: 0.3) were significantly associated with the occurrence of ES. Patients with ES had a statistically significant worse clinical outcome at 3 months follow-up (P = 0.0072). Conclusion: We could formulate an ES prediction tool using the following components: (a) cortical location, (b) large vessel stroke, (c) mRS at admission, (d) anticoagulant use, and (e) presence of hypertension. This tool might help in treating patients at high risk for ES with prophylactic ASD, thereby preventing seizures and their complications.